A model for the acceptance and use of mHealth in South Africa: A UTAUT and TTF perspective - Livhuwani Grace, Mongwe (University of the Witwatersrand, Johannesburg, 2023)
Scaling up high impact community based mHealth interventions is one of the agenda items mentioned in the National Digital Health Strategy of South Africa for the period 2019 -2024. Although many mHealth interventions have been explored, many of them end up in the pilot phase and do not reach full implementation. A common theme which was found as a possible driver of scalability is designing an mHealth application that considers usability and acceptability by users. The purpose of this study was to synthesize a model for the acceptance and use of mHealth in the South African health sector. A positivist research approach was used to test the adoption factors using the Task-Technology Fit (TTF) and the Unified Theory of Acceptance and Use of Technology (UTAUT). Seven factors that could potentially impact the adoption of mHealth technology in South Africa were tested. The data for the study was collected through an online survey questionnaire which was shared through social media platforms. Results of this study were used to answer questions related to factors that have an impact on the adoption of mHealth applications in the health sector in South Africa. The study found that when adoption factors were combined into the UTAUT and TTF model, the only factor that was significant was facilitating conditions. The study findings in this regard were not consistent with other studies and it is therefore recommend that other scholars explore the reasons for these differences. The other factors were found to be significant when bivariate regression was used to compare the factors to the dependant variable of user acceptance and use of mHealth technology. The study further found that the combined model of Task Technology Fit has a positive impact on the adoption of mHealth technology in South Africa. The implication of the finding is that mHealth designers should build the functionalities of the innovation with the idea of making the task that the innovation supports easier to perform
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, MCom Information Systems, University of the Witwatersrand, Johannesburg, 2023
Keywords: IT adoption; mHealth adoption; mHealth; User Acceptance; TTF and UTAUT; UCTD; SDG-3: Good health and well-being